Community mental health nursing training package on body image quality among mental disorders patients - Ibrahim Rahmat; Mohammad Hakimi; Soewadi Soewadi (International Journal of Public Health Science (IJPHS), 2020)
Mental health disorder could affect the physical, mental, social, and spiritual problems, leading to psychosocial issues such as body-image problem. Body-image is a basic need of human being to fulfill and therefore, the multidisciplinary team; physicians, nurses, and family should have adequate knowledge on the body-image. Increasing knowledge by training the nurses and community health volunteers can be performed to address body-image issues in patients with mental disorders among the community. This study held to identify the effects of community mental health nursing (CMHN) and Self-Concept Assessment Guidelines training on nurse and community health volunteer in increasing the body-image quality of patients with mental disorders. This study used pre and post quasi experimental test with nonequivalent control group design. By comparing the pre-test and post-test scores, nurse’s and community health volunteer’s knowledge were increasing after being given training. Data of body image was collected from 129 patients with mental disorder (treatment group of 69 and control group of 60) as volunteers. After the intervention, treatment group (p= 0.033) and control group (p= 0.075) show that significant increase in the quality of body-image only applies to the treatment group. Providing training on CMHN was effective to improve body-image quality of patients with mental disorders.